THE 1965 INDONESIAN KILLING DISCOURSE BY GENERATION 2000 WRITERS - Arimbi, Diah Ariani (Balai Bahasa Jawa Timur, 2011)
The fall of Soeharto?s authority in 1998 has indeed impacted numerous sides of Indonesian life: political, social and cultural. The shifting of authoritative government to the state of ?reformation? and ?democratization? has forced the nation to redefine its authority to its members. This paper aims to look at these public responses which are narrated in contemporary Indonesian fiction. Although fiction may be seen as imaginative production, discursive ideologies can be examined clearly. By examining thematic significant of the narratives about G30S/PKI and the killings aftermath in the literary writings published in post 1998 by contemporary Indonesia writers, who are known as the Generation 2000 writers (who were mostly born in 1970s at least five years after the 1965 incident: also known as the millennials), this paper will attempt to answer whether or not this generation presents shift and creates its own notions of the incident. Abstrak: Jatuhnya kekuasaan Soeharto pada tahun 1998 berdampak pada berbagai sisi kehidupan di Indonesia: politik, sosial, dan budaya. Pergeseran dari pemerintahan yang dulunya otoritatif menjadi pemerintahan yang sarat dengan